If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.13(4x + 2) = 0.05x + 6 Reorder the terms: 0.13(2 + 4x) = 0.05x + 6 (2 * 0.13 + 4x * 0.13) = 0.05x + 6 (0.26 + 0.52x) = 0.05x + 6 Reorder the terms: 0.26 + 0.52x = 6 + 0.05x Solving 0.26 + 0.52x = 6 + 0.05x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.05x' to each side of the equation. 0.26 + 0.52x + -0.05x = 6 + 0.05x + -0.05x Combine like terms: 0.52x + -0.05x = 0.47x 0.26 + 0.47x = 6 + 0.05x + -0.05x Combine like terms: 0.05x + -0.05x = 0.00 0.26 + 0.47x = 6 + 0.00 0.26 + 0.47x = 6 Add '-0.26' to each side of the equation. 0.26 + -0.26 + 0.47x = 6 + -0.26 Combine like terms: 0.26 + -0.26 = 0.00 0.00 + 0.47x = 6 + -0.26 0.47x = 6 + -0.26 Combine like terms: 6 + -0.26 = 5.74 0.47x = 5.74 Divide each side by '0.47'. x = 12.21276596 Simplifying x = 12.21276596
| 5X-15-2=23 | | 1-4x=19-x | | 5x+2y=c | | 7/12-3/8×(9/4)^-1 | | 58+n=58 | | x^2+12x=360 | | 140=(2x+2)(x+4) | | (4x-2)x+78=180 | | 1/3((3.14*(1^2)3) | | 70=(2x+2)(x+4) | | 150w+2=195w-1 | | 2x+0=-6y | | 35=(2x+2)(x+4) | | 12=6(x+1)-8(1-y) | | 1/6p-7=9 | | 24-7p=-6(-4-7p) | | 2x+0=6y | | 2y=-12+6x | | 10x+4+14x=28 | | 1.4x+6=19 | | 7(4x+1)=5x-8x | | dx+(x+2xy^2-2y)dy=0 | | 2/7x=y | | X/4-1.10=4 | | 3(x+3)=6(x-1)-6 | | 2(4-2r)+2=-2(r+5)+8r | | 3/0= | | 12x+8=((2x+3)2)9 | | (d^2+18)(d+4)=-9 | | 2x+5+3=x+10+3 | | (2x-6)(x+4)=35 | | 2/3×5/6×14 |